Subsídios para o estudo do património vinícola de Alijó - a Quinta do Noval - Cardoso, António Barros (2017)
In this article we try to demonstrate the antiquity of an important property that integrates heritage of yesterday and today. The History of Quintas do Noval, in the lands of Alijó, makes us return to the genesis of one of the oldest wine-growing regions in the world and to a wine production unit, which is the depository of the well-known Port wine tradition.